“Universities Devoid of Teaching Staff” Can AI Replace the Role of Professors in the Near Future? - Hamdy, Sherif M.; Zaazou, Zeinab Abbas (The Arab Journal of Administration, 2025)
Artificial Intelligence is rapidly expanding and has the potential to transform all aspects of our social interactions. In the education sector, AI is beginning to create new teaching and learning tools, which are currently being tested in various environments. This paper, intended for education policymakers, explores the impact of AI on education to help guide informed and suitable policy decisions. This study is investigating the impact of Artificial Intelligence in the coming decades, focusing on how this evolving technology will reshape and challenge our academic institutions. This study is also predicting the possibility of replacing university professors in the near future with artificial intelligence programs. The researchers developed a set of different scenarios that oscillate the predicted percentage of replacement over fifty years. The pessimistic scenario predicts a replacement annual rate of 2% for university professors around the world with Artificial Intelligence (AI) programs. The moderate scenario predicts a replacement rate of 1%, and the optimistic scenario predicts a replacement rate of 0.5%. The researchers also came up with a mathematical formulation using Gaussian distribution function to obtain the normal distribution of the estimated replacing curve and parameters. Finally, they developed an action plan of 10 steps presenting implications for the rational use of technology and the synergy between skilled and well-trained man-power and AI programs in the educational sector.